The evaluation of bank performance using a multicriteria decision making model: a case study on Lithuanian commercial banks - Stankevičienė, Jelena; Mencaitė, Evelina (Technological and Economic Development of Economy, 2012)
The paper presents an attempt to adopt a muticriteria decision making approach, particularly the Analytical Hierarchy Process (AHP) model, and to evaluate the performance of banks. The model is based on a system of various qualitative and quantitative criteria and their mutual relations. A system of indicators is created and described and each indicator is assigned a different degree of significance taking into account the needs and priorities of both internal and external evaluators. Model adaptation to Lithuanian market and an empirical test enabled to compare banks between each other, reveal their ranking and identify the banks taking leading positions in the market. The conducted research has concluded that the Analytical Hierarchy Process (AHP) model is appropriate for using it in the process valuating bank performance.